Financial turbulence Some lessons regarding deposit insurance - Schich, Sebastian (OECD Publishing, 2008)
One specific aspect of financial safety nets that has been in the spotlight of late is deposit insurance. As events in markets are still unfolding, it is too soon to draw definitive conclusions regarding the effects of the crisis and the adequacy of financial safety nets, including deposit insurance arrangements. Nonetheless, preliminary suggestions for policy are emerging and the article singles out four areas for special attention. First, as regards coverage, deposit insurance systems with low levels of coverage and/or partial insurance may not be effective in preventing bank runs. Second, for an explicit deposit insurance system to be effective, depositors need to understand the extent of and limits to existing deposit protection schemes. Third, when different institutions are entrusted with responsibilities that are relevant in a crisis situation, ex ante arrangements delimiting the scope of the different responsibilities as well as the respective powers may not be sufficient to ensure co-ordination that is as close and smooth as needed. Fourth, the question as to whether a specific bankruptcy regime for banks is needed remains an important issue
Keywords: Finance and Investment